ANALYSIS OF THE IMPLEMENTATION OF SHARIA FINTECH BASED ON ‎FATWA DSN MUI CASE STUDY OF PT. ALAMI FINTEK SHARIA - Muhammad Karin Aulia Rachman; Hartomi Maulana (University of Darussalam Gontor, 2021)
This study aims to analyze the application of sharia fintech based on fatwa DSN MUI 117/DSN-MUI/II/2018, a case study at PT. Alami Fintek Sharia. Financial technology (FinTech) is the result of a combination of financial services and technology, which is ultimately changing the role of business models from conventional to moderate. There is also the presence of fintech sharia in Indonesia to answer market opportunities and solve business problems in the field of financial technology. This study aims to determine the implementation of fintech sharia at PT. Alami Fintek Sharia and to analyze the implementation of fintech sharia at PT. Alami Fintek Sharia based on fatwa DSN MUI. This research methodology uses primary data and secondary data. The method used in this research is qualitative with the type of content analysis. Where content is obtained from interview scripts, as well as data publication from DSN MUI and OJK Indonesia. The results of this study indicate that PT. Alami Fintek Sharia has implemented fintech sharia based on fatwa DSN MUI 117/DSN-MUI/II/2018.Keywords: Fintech Sharia, OJK, DSN MUI, PT.ALAMI, Fintech